2019
DOI: 10.3346/jkms.2019.34.e208
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Partial Splenic Embolization in Hepatocellular Carcinoma Patients with Thrombocytopenia Who Underwent Transarterial Chemoembolization

Abstract: Background Performing transarterial chemoembolization (TACE) is difficult with the occurrence of thrombocytopenia in cirrhotic patients with hepatocellular carcinoma (HCC). We aimed to evaluate the long-term efficacy and safety of partial splenic embolization (PSE) combined with TACE in patients with HCC with severe thrombocytopenia related to splenomegaly. Methods We conducted a case–control study consisting of 18 HCC patients with severe thrombocytopenia (< 50 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Hematological abnormalities caused by hypersplenism may limit HCC treatment options and delay the treatment implementation. [ 12 , 13 ] People with severe hypersplenism have a higher risk of varicose vein rupture and bleeding, and even death. [ 14 , 15 ] Still, the use of β-blockers or antibiotics for medical treatment of severe hypersplenism has no definite benefit, [ 15 ] making invasive treatment an important option for hypersplenism.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological abnormalities caused by hypersplenism may limit HCC treatment options and delay the treatment implementation. [ 12 , 13 ] People with severe hypersplenism have a higher risk of varicose vein rupture and bleeding, and even death. [ 14 , 15 ] Still, the use of β-blockers or antibiotics for medical treatment of severe hypersplenism has no definite benefit, [ 15 ] making invasive treatment an important option for hypersplenism.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study were positive to improve thrombocytopenia without significant adverse effects 1. However, it might need cautious interpretation of the results because of small study numbers at baseline and high rates of follow-up loss (36.7%) during the follow-up periods.…”
mentioning
confidence: 72%
“…Regarding safety of PSE in this study, the Child-Turcotte-Pugh scores within 6 months after treatment in the PSE group were significantly higher than those in the non-PSE-group. However, there was no significant difference of severe adverse events occurred in the two group: 11.1% and 9.7% of patients in the PSE and non-PSE groups, respectively 1…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…showed that PSE combined with TACE effectively induced and maintained improvements in thrombocytopenia and reduced the need for platelet transfusion. 8 PSE has been reported to be effective not only for improving cytopenia, but also for enhancing hepatic functional reserve and hepatic protein synthesis by decreasing splenic blood flow and increasing hepatic artery and superior mesentery artery blood flow. 9,10 Moreover, PSE can induce activation of host immunity 11 and promote anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%